Viral Agents in Children Presenting with Signs and Symptoms of Respiratory Infections in the Ashanti-Akyem North District of Ghana - Annan, Augustina Angelina (2013)
A Thesis submitted to the Department of Clinical Microbiology, Kwame Nkrumah University of Science and Technology, Kumasi,in partial fulfillment of the requirements for the degree of Doctor of Philosophy.